Matematiskt tankesätt inom den samiska kulturen : utifrån samiska slöjdares och renskötares berättelser - Jannok-Nutti, Ylva (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2007)
The purpose of this licentiate thesis is to study mathematical cultural knowledge within the sámi culture. The study describes and analyzes how sámi handicrafters and reindeer herders express their mathematical thinking, and how they express the learning of the mathematical cultural knowledge. The learning will be analyzed from the point of learning within a cultural context with focus on the mathematical knowledge, and knowledge transforming trough generations.The empirical study is collected through qualitative interviews and literature study. The results are based on 10 interviews with sámi handicrafters and reindeer herders. The Sámi handicrafters and reindeer herders were chosen by me trough personal contacts. The persons are from the communities of Kiruna, Gällivare and Jokkmokk. The choice to focus on sámi handicrafters and reindeer herders are from my experiences from an earlier study. The interviews are recorded with recorder, video or by notes. The interviews were conducted according to two strategies. There strategy one focused on the persons´ life story. The person was asked to tell about her/his life from an yearly base. The second strategy was based on a question form with guiding questions.The results are presented in seven categories, Alan Bishop's sex activities: counting, locating, measuring, designing, playing and explaining, and a category: knowledge and learning. The results and, and a category: knowledge and learning. The results show that there are several conceptions for the reindeer herds according to the approximate number of reindeer in the herd. The special reindeer are used as an aid for the counting or approximation, and as an aid for the localisation of reindeer. The numbers of marked reindeer calves are counted trough marks on a wood-stick, by parts from the ear of the marked calves', or by notes on a paper. Locating in the nature is by well-known objects in the nature, by the wind, or by the rivers. The cardinal points are after the landscape, after the rivers or lakes, and the ...